Associations between smoking and coronary heart disease: mediating role of RDW - Mingfeng Ma; Mingfeng Ma; Yue Wu; Xingmin He; Miaomiao Zhang; Yanlin Han; Renwei Guo; Shaojie Li (Frontiers Media S.A., 2024)
IntroductionPrevious studies have demonstrated that both smoking and coronary heart disease (CHD) are linked to red cell distribution width (RDW). However, the role of the RDW in the association between smoking and CHD remains unclear. This study investigates the role of RDW in the association between smoking and coronary heart disease.MethodsData from 13,080 adults aged 40-80 years were analyzed from the National Health and Nutrition Examination Survey (NHANES) conducted between 2006 and 2017. Statistical methods included regression analysis, restricted cubic spline curve (RCS), subgroup analysis, and mediation analysis.ResultsResults showed higher RDW levels in participants with smoking and/or CHD than in those without. Smoking status was positively associated with RDW and CHD even after adjusting for potential confounders. A nonlinear relationship between RDW and CHD was observed (P for nonlinear <0.001). Subgroup analysis revealed that sex influenced the relationship between smoking and CHD (p = 0.0284). Mediation analysis showed that increased RDW levels mediated the association between smoking status and CHD (PM = 2.1959%, ACME = 0.000694, 95% CI = 0.000262-0.001259, p < 0.001).DiscussionOur research showed that smoking, RDW, and CHD are interrelated, with RDW playing as a mediator, offering a novel perspective for the prevention and management of CHD.